English in mind : workbook 3 - Puchta, Herbert; Stranks, Jeff; Carter, Richard; Lewis-Jones, Peter (Cambridge: Cambridge University Press, 2010)
This second edition updates a course which has proven to be a perfect fit for classes the world over.
Keywords: English language -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; English language